A Case–control Study of Diphtheria in the High Incidence City of Hyderabad, India. Issue 3 (March 2016) - Allam, Ramesh Reddy; Uthappa, Chengappa Kechamada; Duerst, Rebecca; Sorley, Evan; Udaragudi, Prasada Rao; Kampa, Shankar; Dworkin, Mark S.
Abstract : Background: India accounts for approximately 72% of reported diphtheria cases globally, the majority of which occur in the state of Andhra Pradesh. The aim of this study is to better understand lack of knowledge on diphtheria vaccination and to determine factors associated with diphtheria and low knowledge and negative attitudes. Methods: We performed a 1:1 case–control study of hospitalized diphtheria cases in Hyderabad. Eligible case patients were 10 years of age or older, resided within the city of Hyderabad and were diagnosed with diphtheria per the case definition. Patients admitted to the hospital for nonrespiratory communicable diseases and residing in the same geographic region as that of cases were eligible for enrolment as controls Results: There were no statistical differences in disease outcome by gender, education, economic status and mean room per person sleeping in the house in case and control subjects. Not having heard of diphtheria (adjusted odds ratio: 3.56; 95% confidence intervals: 1.58–8.04] and not believing that vaccines can prevent people from getting diseases (adjusted odds ratio: 3.99; 95% confidence intervals: 1.18–13.45) remained significantly associated with diphtheria on multivariate analysis. Conclusion: To reduce the burden of diphtheria in India, further efforts to educate the public about diphtheria should be considered.